The Phenomenological and the Symbolical in Richir’s “Quasi-Theology” - Ekweariri, Dominic Nnaemeka (Religions, 2023)
If a new generation of phenomenologists (Emmanuel Levinas, Michel Henry, Jean-Luc Marion, Jean-Louis Chrétien, Jean-François Courtine) in France sought to overcome the “methodic atheism” imposed on the phenomenological method by the fathers of phenomenology, it was at the price of going beyond experience immanent to existence which targeted the invisible, and therefore of lacking a discourse on the critical restriction of the phenomenological method and on the points of contact between phenomenology and theology. The task of this paper is to show how this lack is overcome by Marc Richir’s “quasi theology” viewed from his articulation of the relationship between the phenomenological and the symbolical. This paper argues that whereas for the new French phenomenologists it is usually a question of a subreptitious crossing from one discipline to another, in Richir, what we have is an enigmatic relationship of the overlap between phenomenology and the symbolical. While Richir was only interested in the articulation of the relationship between the phenomenological, the symbolical and the absolute transcendence, his thoughts motivate us to explore, following Emmanuel Falque’s approach, the reciprocal transformation between phenomenology and theology. The paper concludes, on the one hand, that experience remains the immanent ground for phenomenology and theological science and, on the other, that Richir’s approach could be understood as a “metaphysical phenomenology”.